The Link Between Ontology and Sociohistorical Knowledge: Cornelius Castoriadis’ Contributions to the Imaginary Dimension and the Project of Autonomy - Hernández Chávez, Ramsés (2025)
A problem that Cornelius Castoriadis developed in depth was that of the inseparable link between imaginary institution, ontology, and forms of knowledge of society and history, which he conceptualizes as the sociohistorical. From the analysis of the foundations of Marxism, he locates a tendency of knowledge of the sociohistorical characterized by a deterministic ontology of being. Likewise, as part of the Graeco-Western creation of the project of social and individual autonomy, he identifies an ontology and a conception of the sociohistorical that is not deterministic, but centered on the imaginary condition or faculty. As for this conception of the sociohistorical, he develops it in his main work, The Imaginary Institution of Society, to later give content to his ontology of the living centered on the imaginary from the category of for-itself. This paper explores the content of this ontology and its implications for the knowledge of the sociohistorical, particularly the criteria of distinction between autonomous and heteronomous forms of the sociohistorical. The objective is to situate the contributions of this author for the discussion and understanding of the existing link between ontology, knowledge of the sociohistorical and effective sociohistorical reality.